2004
DOI: 10.1387/ijdb.15272387
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of epidermis differentiation in Drosophila.

Abstract: In arthropods, the animal body is isolated from the external environment by a protective exoskeleton called the cuticle. The cuticle of young larvae has certainly been the most scrutinized structure in Drosophila and genetic studies of the pattern of cuticular extensions has provided the main source of our comprehension of the control of embryonic development. However, the complex structure of the cuticle remains poorly understood and analysis of the underlying epidermis has started only recently. Here I revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 109 publications
1
42
0
1
Order By: Relevance
“…After the secretion (stage 16) and assembly (stage 17) of the wild-type cuticle it functions as a nonpermeable barrier for antibodies (29). TEM analysis revealed that indeed all layers of the DmMANF ⌬96mz mutant cuticle were disorganized (Fig.…”
Section: Embryos Lacking Both Maternal and Zygotic Dmmanf Results In Cmentioning
confidence: 99%
“…After the secretion (stage 16) and assembly (stage 17) of the wild-type cuticle it functions as a nonpermeable barrier for antibodies (29). TEM analysis revealed that indeed all layers of the DmMANF ⌬96mz mutant cuticle were disorganized (Fig.…”
Section: Embryos Lacking Both Maternal and Zygotic Dmmanf Results In Cmentioning
confidence: 99%
“…Furthermore, none of the encoded collagens closely resembles the worm cuticle forms. The Drosophila cuticle is a stratified structure comprising an envelope layer, a proteinaceous epicuticle, and a procuticle rich in chitin (polymer of Nacetylglucosamine) (11). The envelope functions as a support for subsequent cuticle deposition, and the epicuticle and the procuticle together stiffen the exoskeleton.…”
mentioning
confidence: 99%
“…The metabolic state and gene expression in these cells directed or regulated by the nutrient dependence and environmental effect are coordinated toward this fate for cells, and imprint onto the subsequent organogenesis. During organogenesis, the cells of embryonic ectoderm give rise to neural progenitors in the dorsal side and epidermal progenitors in the ventral side in vertebrates [16], while also give rise to neural cells [17] and epidermal cuticle in Drosophila [18]. In this regard, the regulation of both cell state and gene classes in ectoderm with proposed nutrient gradient during gastrulation fits with the developmental outcome of phenotype, also supporting the rationality of the theory.…”
Section: Phenotypic Fates Of Three Germ Layers In Gastrulamentioning
confidence: 58%
“…The endoderm is destined to differentiate into the epithelial lining of digestive tract, associated glands and respiratory system in both vertebrates [14] and Drosophila [15]. The ectoderm is destined to differentiate into the neural progenitors and epidermal progenitors in vertebrates [16], and to neural cells [17] and epidermal cuticle in Drosophila [18]. The mesoderm is destined to differentiate into the bones, muscles [19], and adipose tissues [20] in vertebrates, and to muscles in Drosophila [21].…”
Section: Nutrient Preserving the Trilaminar Fates In Gastrula Versus mentioning
confidence: 99%